A performance-based optimization approach for diffusive surface topology design. Issue 3 (September 2021) - Shtrepi, Louena; Mendéz Echenagucia, Tomás; Badino, Elena; Astolfi, Arianna
Different numerical techniques have been used in the last decades for the acoustic characterization and performance optimization of sound diffusive surfaces. However, these methods require very long calculation times and do not provide a rapid feedback. As a result, these methods can hardly be applied by designers at early stages of the design process, when successive design iterations are necessary from an aesthetic point of view. A suitable alternative could be the use of parametric modeling in combination with performance investigations during the design process of sound diffusive surfaces. To this aim, this study presents a design process for diffusive surfaces topology optimization based on the combination of parametric models and geometrical acoustic simulations. It aims to provide architects and designers with rapid visual feedback on acoustic performances at a preliminary stage of the design process. The method has been tested on different case studies, which have been modelled based on geometric guidelines for diffusive surface optimization. The sensitivity of the method showed that it could be a very useful tool for comparisons among surface design alternatives. Finally, the advantages and limitations of the integrated optimization in comparison with conventional optimizations are discussed.